Pemanfaatan Media Sosial untuk Digital Campaign dan Webinar dalam Meningkatkan Disability Awareness pada Masa Pandemi COVID-19 Bersama Komunitas Peduli Inklusi Nusantara (KOPINUS) - Haqi, Haditio Rasyid; Nurhasanah, Nurhasanah; Fridayanti, Nofia; Saptono, Adinda Rachmawati Ayuni (PUNDIMAS: Publikasi Kegiatan Abdimas, 2024)
The use of technology is growing for many individuals. Due to advanced technology, there are many things that can be utilized, including the use of social media to carry out digital campaigns and webinars to increase awareness of disabilities during the COVID-19 pandemic. The method used in this report goes through three stages, namely preparation, implementation, and monitoring and evaluation. In the preparation stage, the PKM team conducted initial online observations regarding KOPINUS in more depth. Then, at the implementation stage, starting with designing the program first from the PKM team and also trying to get information about the needs needed by KOPINUS, through FGD (Focus Group Discussion). The final stage is the monitoring and evaluation stage, the PKM team monitors the registration process for online campaign volunteers and webinar activities. The research results show that with digital campaigns, webinars, eight KOPINUS programs, the use of social media has succeeded in increasing public awareness of issues related to disabilities through managing social media Twitter and Instagram. As part of the disability community, KOPINUS plays an important role in disseminating information and supporting the campaigns that have been carried out.